Synthesis and Characterization of Proteolytic Enzyme Loaded on Silver Nanoparticles - Salim Al-Shmgani , Hanady; Ashij , Mohammed A.; Khalil, Khalil A. A.; Mohammed, Hamdoon A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Bromelain is a proteolytic enzyme rich in cysteine proteases, extracted from the stem and fruit of pineapple (Ananas comosus). There are several therapeutic applications of the bromelain enzyme, where it has anti-inflammatory, anti-cancer, and antimicrobial activity, reduces joint pain, and accelerates wound healing. In the current study, bromelain enzyme was loaded on silver nanoparticles (Br-AgNPs) prepared using the citrate-reduction Turkevich method. Different characterization analyses were performed, including UV-Vis spectrophotometers, FTIR, SEM, and XRD analyses. Moreover, the antioxidant activity of prepared Br-AgNPs was evaluated by DPPH assay. The results of UV-Vis showed a peak at 434 nm, which referred to the AgNPs formation, and FTIR results revealed groups of (C=O, C=C) at 1519.91 and 1539.20, respectively, and the amine group at 1384.89 and the flavonoids group at 1357.89. SEM results exhibit that the synthesized Br-AgNPs were spherical in shape, with average sizes of about 84.73 nm. Also, the AgNPs were crystalline in nature with face-centered cubic symmetry. The synthesized BR-AgNPs showed strong in vitro antioxidant activity in a dose-dependent manner. In conclusion, successfully synthesized silver nanoparticles and bromelain had a potent antioxidant effect and may be a possible therapeutic agent for many diseases in the future.